Chemopreventive and therapeutic effects of Hippophae rhamnoides L. fruit peels evaluated in preclinical models of breast carcinoma - Dvorska, Dana; Sebova, Dominika; Kajo, Karol; Kapinova, Andrea; Svajdlenka, Emil; Goga, Michal; Frenak, Richard; Treml, Jakub; Mersakova, Sandra; Strnadel, Jan; Mazurakova, Alena; Baranova, Ivana; et al. (Frontiers in Pharmacology, 2025)
BackgroundCancer remains a major global health challenge, necessitating innovative prevention and treatment approaches. Certain plants, adapted to specific environments, may exhibit bioactive properties with potential anticancer applications.HypothesisSeaberry (Hippophae rhamnoides L.) fruit peels may exert anticancer effects in breast carcinoma (BC) models through the additive or synergistic actions of their unique secondary metabolites.MethodsH. rhamnoides fruit peel extracts were analyzed using the LC-DAD-MS and LC-DAD techniques to profile the content of carotenoids and flavonoids, respectively. The preclinical study evaluated seaberry fruit peel extracts in BC models: (1) a syngeneic 4T1 mouse breast adenocarcinoma model (triple-negative), (2) a rat model of chemically induced mammary carcinogenesis, and (3) in vitro studies with MCF-7 (hormone receptor-positive) and MDA-MB-231 (triple-negative) BC cell lines.ResultsLC-DAD-MS and LC-DAD analyses identified dominant metabolites, including isorhamnetin, quercetin glycosides, kaempferol glycosides, catechin, zeaxanthin, and lutein. In the 4T1 mouse model, seaberry treatment resulted in a significant, dose-dependent reduction in tumor volume (43% and 48% compared to controls) and a decrease in the mitotic activity index. Serum cytokine analysis showed dose-dependent reductions in IL-6, IL-10, and TNF-α. In the rat chemopreventive model, high-dose seaberry improved cancer prognosis by reducing the ratio of poorly differentiated tumors and increasing caspase-3 and Bax expression while decreasing Ki-67 and malondialdehyde levels. Both treatment doses elevated the Bax/Bcl-2 ratio and reduced the expression of cancer stem cell markers CD44, EpCam, and VEGF compared to controls. Epigenetic analyses revealed histone modifications (H4K16ac, H4K20me3) and altered methylation of tumor-suppressor genes (PITX2, RASSF1, PTEN, TIMP3). Microarray analysis (758 miRNAs) identified beneficial changes in nine oncogenic/tumor-suppressive miRNAs, including miR-10a-5p, miR-322-5p, miR-450a-5p, miR-142-5p, miR-148b-3p, miR-1839-3p, miR-18a-5p, miR-1949, and miR-347. In vitro, ethanolic seaberry extract conferred partial resistance to cisplatin-induced cytotoxicity in MCF-7 and MDA-MB-231 cells at IC50 concentrations.ConclusionThis study of H. rhamnoides in rodent BC models shows promising data but requires rigorous, long-term validation. Integrating plant-based nutraceuticals into oncology necessitates precise cancer-type profiling and patient stratification for effective personalized treatments.